(untitled) (Docentes 2.0 Journal, 2020)
Considering the current global emergency that endangers the sustainability of current and future generations, it is important that students are trained from the complex socioformative paradigm and competences for Sustainable Development allowing them to face up the challenges of unsustainability in the exercise of your professions. In this article, it is described the importance of Education for Sustainable Development (ESD), the key competences for sustainability that students must acquire during their academic progress and what knowledge teachers must handle to train in these competences. The curricular programme of many universities around the world have been transformed. International organizations have promoted development projects at the level of public and educational politics associated with sustainability. These contributions open the doors to reflections, debates and actions that consolidate education for Sustainable Development as a “motor of change” for citizens can be provided with the necessary tools to consolidate the binomials allowing to maintain a viable world: criticism and creativity, participation (inclusion) and democracy, conflict management and peace, respect for the environment and (bio) diversity.